New considerations of the systematics of the family Holophryidae (Protozoa, Ciliophora, Prostomatea) with a description of Holophrya paradiscolor sp. nov. and a redescription of Pelagothrix plancticola. Issue 1 (31st December 2022) - Jiang, Limin; Wang, Congcong; Warren, Alan; Ma, Honggang; Hu, Xiaozhong
Abstract : The diversity of the family Holophryidae is relatively poorly known due to a lack of studies using modern methods, the paucity of taxonomically informative characters for species circumscription, and the morphological similarity among holophryids. In the present study, two holophryid ciliates, namely Pelagothrix plancticola and Holophrya paradiscolor sp. nov., isolated from two freshwater ponds in Qingdao, China, are reported. The morphology of both species was described based on living observation and protargol staining, and their molecular phylogeny was analysed using SSU rRNA gene sequence data. Pelagothrix plancticola has never been redescribed since its establishment. Based on new data, an improved diagnosis of P. plancticola is supplied. Holophrya paradiscolor sp. nov. is distinguished by a combination of features including a single macronucleus, the absence of endosymbiotic green algae, and the presence of two types of extrusomes. Following the addition of two new sequences, the molecular phylogeny of the family Holophryidae was analysed. Finally, the information on the habitats and geographic distribution of holophryids was reviewed. http://zoobank.org/urn:lsid:zoobank.org:pub:3D2D3902-58BA-47D7-A5DE-FEA0A5163384